VIKSIT BHARAT 2047: DRIVING GROWTH THROUGH ESG LEADERSHIP (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
In response to the evolving business landscape, companies have expanded their focus beyond profit generation to actively contributing to environmental, social, and governance (ESG) practices. This strategic shift demonstrates a commitment to sustainable and responsible engagement with the broader community, transcending financial success alone. The integration of ESG practices is instrumental in enhancing a firm's financial performance by mitigating risks, implementing cost-effective sustainable measures, and attracting socially conscious investors. We try to evaluate the impact of ESG practices on a firm’s financial performance by taking NSE top 100 companies for the year 2021-22. Our study uses ordinary least square linear regression and concludes positive impact of ESG on firm performance. Thus, in the contemporary business landscape, companies should consider ESG consideration as an essential tool to gaining competitive edge.